(untitled) (Research, Society and Development, 2020)
The public water supply in the municipality of Sete Lagoas (MG) is characterized as hard due to the limestone characteristics of the subsoil, generating an unpleasant taste and causing a high consumption of bottled mineral water. The wide variety of brands available in the municipality raises questions about their quality. Thus, this study aimed to evaluate the physical-chemical, microbiological characteristics and verify the labeling information in mineral water samples filled in a volume of 20 liters sold in the municipality of Sete Lagoas-MG. Eighteen different samples were analyzed in triplicate. The determination of total, thermotolerant coliforms, Escherichia coli and Pseudomonas aeruginosa was performed using the Most Probable Number (NMP) technique and Enterococcus sp. by the filter membrane method. The analysis of hardness and total alkalinity were performed by the volumetric method with visual indicator, the concentration of minerals (calcium, magnesium, sodium and potassium) by atomic absorption spectrometry and the pH measurement using a pH meter. It was found that eight samples were unsuitable for consumption, and seven showed contamination by Enterococcus sp. and three by P. aeruginosa. The pH, hardness and alkalinity were in accordance with the standards established for drinking water. For most samples, the values ​​found for the analyzed minerals varied considerably when compared to what was stated on the label. It was concluded that some brands were at odds, whether for microbiological or physical-chemical reasons. Inspection, periodic analysis and application of good practices are essential to provide mineral water of adequate quality for human consumption.